2015
DOI: 10.1073/pnas.1510060112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for rapid passive-dynamic prey capture in a pitcher plant

Abstract: Plants use rapid movements to disperse seed, spores, or pollen and catch animal prey. Most rapid-release mechanisms only work once and, if repeatable, regaining the prerelease state is a slow and costly process. We present an encompassing mechanism for a rapid, repeatable, passive-dynamic motion used by a carnivorous pitcher plant to catch prey. Nepenthes gracilis uses the impact of rain drops to catapult insects from the underside of the canopy-like pitcher lid into the fluid-filled trap below. High-speed vid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 47 publications
0
29
0
1
Order By: Relevance
“…As a conclusion it can be said that the Venus flytrap has evolved a remarkable trapping system that functions as well in air as under water, and which can be considered as an optimized system for nutrient acquisition of a carnivorous plant growing in seasonally inundated habitats. Similar reports on carnivorous plants with traps functioning under different environmental conditions are, e.g., the resinous Roridula sticky traps [ 37 ] and the rainwater-dependent pitfall trapping systems in Nepenthes [ 38 39 ]. The Dionaea trap is not “only” a “simple” snap trap but possesses different snapping modes, movement mechanics and actuation principles, which greatly broadens our understanding of this (in)famous carnivore and opens up novel perspectives for future studies.…”
Section: Discussionmentioning
confidence: 53%
“…As a conclusion it can be said that the Venus flytrap has evolved a remarkable trapping system that functions as well in air as under water, and which can be considered as an optimized system for nutrient acquisition of a carnivorous plant growing in seasonally inundated habitats. Similar reports on carnivorous plants with traps functioning under different environmental conditions are, e.g., the resinous Roridula sticky traps [ 37 ] and the rainwater-dependent pitfall trapping systems in Nepenthes [ 38 39 ]. The Dionaea trap is not “only” a “simple” snap trap but possesses different snapping modes, movement mechanics and actuation principles, which greatly broadens our understanding of this (in)famous carnivore and opens up novel perspectives for future studies.…”
Section: Discussionmentioning
confidence: 53%
“…For example, Bauer et al . () demonstrated that the pitcher lid of N. gracilis is adapted to exploit the impact of rain drops for capturing insect prey. The lid of this species functions as a rain‐driven torsion spring, flicking insects into the pitcher during heavy rain.…”
Section: Divergent Evolutionmentioning
confidence: 99%
“…Modifications in trap geometry may enable the utilization of novel nutrient sources, analogous to well-known examples in animals, such as the diverse beak shapes of Darwin's finches and the various adaptations of cichlid fish in the African Great Lakes. For example, Bauer et al (2015a) demonstrated that the pitcher lid of N. gracilis is adapted to exploit the impact of rain drops for capturing insect prey. The lid of this species functions as a rain-driven torsion spring, flicking insects into the pitcher during heavy rain.…”
Section: Divergent Evolutionmentioning
confidence: 99%
“…Considering the significant differences in macromorphology, microstructure and their corresponding functions, the pitchers can be typically divided into four parts: a canopy-like lid, a collar-formed peristome, a slippery zone and a digestive zone [ 5 , 6 ]. The canopy-like lid prevents the inner pitcher from being contaminated [ 7 ], also acts as a catapult to make insects fall into the pitcher below [ 8 ]. The collar-formed peristome consists of radial ridges, which extend towards the pitcher inside [ 2 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%